As noções de finitude em Michel Foucault - Sendacz, Roberta (2016)
This paper contemplates the study of the “finitude” notion in Michel Foucault, especially in The Order of Things (1966), based on the “analytic of finitude” idea. Modernity is the proper territory for the idea of finitude to be explained in the philosopher’s thought. The modern episteme, a priori record of the human sciences, is its soil